Visual analog scale evaluation at pressure pain reception in maxillofacial region: Evaluation in non-symptomatic subjects - SUGISAKI, Masashi; TANABE, Haruyasu; IKAI, Akihiro (Journal of the Japanese Society for the Temporomandibular Joint, 1995)
To evaluate the nature of pain at pressure pain threshold (PPT), we measured the intensity of the pain on the visual analog scale (VAS) at pressure pain reception in the maxillofacial region. Fifty volunteers (men: 13, women: 37) with no symptoms of temporomandibualr disorders were examined in the seven setting measurement points of the maxillofacial region. The subjects PPTs were measured using the algometer at a constant rate of 500g/cm2·s and the intensity of the pain on the VAS at that time was recorded. The distance of the mark from the left end of the scale was defined as the VAS score. The Results showed that the VAS scores in the points of the forehead, the anterior bundles of the temporal muscle, the posterior margin of the mandibular ramus and the Libman's point were significantly different from those of other measurement points. Among of the points in the inferior and mid portion of the masseter muscle and the lateral pole of the condyle, the VAS scores were not found to be significant ly different. In addition, from the significant correlations of the VAS scores in all measurement points, it is considered that a person with higher VAS score of the pain at pressure pain reception is inclined to evaluate the VAS score high in any measurement points in the maxillofacial region.